J. M. Coetzee's Disgrace and the Temporality of Injury. Issue 3 (27th May 2017) - Boese, Stefanie
ABSTRACT: Contrasting the historical injuries of apartheid politics with contemporary violence in postapartheid South Africa, J. M. Coetzee's novel Disgrace explores how competing past and present claims of victimization may be reconciled. While critics generally remark on the inability of existing legal frameworks to adequately address the way in which experience is shaped by identity, few have remarked on the temporal dimension of postapartheid South African social relations. This essay considers the way in which temporality modifies and undermines the role of identity claims in contemporary frameworks of justice. It argues that historical injury must be understood not as belonging to identity but as mediated by the temporality of embodied experience. By recognizing historical injury not as static object but as lived affective orientation toward the present, this essay suggests we might create a productive opening for rethinking existing social justice paradigms.